2020
DOI: 10.13189/ujer.2020.080340
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Number Concepts through Learning Connected Mathematics (CM): A Local Cultural Approach

Abstract: Mathematics becomes an important subject in elementary school. Numbers are one part of school mathematics. Learning that links between concepts and what is close to students' minds makes it easy for students in the process of reaching concepts. This is CM based on local culture. This research used a 2x2 factorial design. The population is all elementary school students from the "Integrated Islamic Foundation" in Bengkulu City. Samples were taken by using an intact group technique. The total sample is 60 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…There are differences in mathematical abilities for students who are taught with realistic mathematics approaches compared with students taught with traditional learning. Also, the mathematical skills of ethnomathematical oriented students were better than those who were non-ethnomathematical oriented [26]. This gives confidence that realistic mathematics learning and ethnomathematics approaches have a positive influence on students' mathematical abilities in elementary schools.…”
Section: Figure 1: Example Of Tabutmentioning
confidence: 68%
See 1 more Smart Citation
“…There are differences in mathematical abilities for students who are taught with realistic mathematics approaches compared with students taught with traditional learning. Also, the mathematical skills of ethnomathematical oriented students were better than those who were non-ethnomathematical oriented [26]. This gives confidence that realistic mathematics learning and ethnomathematics approaches have a positive influence on students' mathematical abilities in elementary schools.…”
Section: Figure 1: Example Of Tabutmentioning
confidence: 68%
“…It applies a similar effect on students' learning activities [22]. Through learning that is close to students' minds and the ethnomathematics approach can improve problemsolving skills [23], mathematical communication [24], and overcome mathematical difficulties [25] [26] Also, it was to improved mathematical abilities.…”
Section: Figure 1: Example Of Tabutmentioning
confidence: 99%
“…These students are able to rediscover mathematical concepts and their perceptions of mathematics as a scientific discipline [23]. Also, the ethnomathematics approach assisted by YouTube media contributes to improving students' mathematical skills, especially problem solving [18], and understanding mathematical concepts [24]. Thus, we believe that mathematics learning suitable for junior high school students during the COVID-19 pandemic is a local cultural approach assisted by YouTube.…”
Section: Figure 8 Solution To the Third Questionmentioning
confidence: 99%
“…Integrated learning based on daily life positively affects the ability to understand mathematics (Andriani et al, 2020). It is shown that the average score and understanding of mathematical concepts of students who are taught with realistic learning is higher than that of students who are taught using conventional learning models.…”
Section: Introductionmentioning
confidence: 99%